Closing the Matter and Energy Cycle in the Sugar/Alcohol Sector - Pacheco, Jessé Morais; Hoff, Debora Nayar (Sustainability in Debate, 2013)
The sustainable development must be seen from the understanding of the multiple relation that occurs between the natural environment and the other actors of the system. In agroindustrial systems, this is a serious issue because of the close dependence between production processes and natural elements. The objective of this paper is to organize, from other published studies, the main energy and material flows already identified within the sugarcane sector. Then, it present an overview of the degree of closing cycle regarding that sector. This work is an descriptive research that uses secondary data and the results demonstrates: i) the high rates of reutilization of bagasse of sugar cane and water allows the cogeneration of energy and the low capitation of water from natural resources; ii) the possibility of treatment for by-products allows the reutilization in other processes, as biodigestion and fertigation.